The Role of Capital Structure on Investment Opportunity Set, Earnings Growth and Earnings Quality - Siti Aulia, Lia (Universitas Pamulang, 2024)
This research intends to determine the influence of Investment Opportunity Set and Earnings Growth on Earnings Quality with Capital Structure as a moderating variable. Infrastructure companies listed on the Indonesia Stock Exchange during 2018-2022. This study used a purposive sampling technique with a total sample of 95 observations obtained. The analysis technique used in this research is Descriptive Statistical Analysis using Eviews applications. The results showed that the Investment Opportunity Set influences earnings quality. Meanwhile, earnings growth does not influence earnings quality. Capital Structure can weaken the effect of earnings growth on earnings quality. This study reveals that earnings growth does not affect earnings quality, while the Investment Opportunity Set affects earnings quality. Capital structure can strengthen the effect of investment opportunity on earnings quality, and capital structure can weaken the effect of earnings growth on earnings quality.